AMPK as a Potential Therapeutic Target for Intervertebral Disc Degeneration - Wang, Zhen; Shen, Jianxiong; Feng, Erwei; Jiao, Yang (Frontiers in Molecular Biosciences, 2021)
As the principal reason for low back pain, intervertebral disc degeneration (IDD) affects the health of people around the world regardless of race or region. Degenerative discs display a series of characteristic pathological changes, including cell apoptosis, senescence, remodeling of extracellular matrix, oxidative stress and inflammatory local microenvironment. As a serine/threonine-protein kinase in eukaryocytes, AMP-activated protein kinase (AMPK) is involved in various cellular processes through the modulation of cell metabolism and energy balance. Recent studies have shown the abnormal activity of AMPK in degenerative disc cells. Besides, AMPK regulates multiple crucial biological behaviors in IDD. In this review, we summarize the pathophysiologic changes of IDD and activation process of AMPK. We also attempt to generalize the role of AMPK in the pathogenesis of IDD. Moreover, therapies targeting AMPK in alleviating IDD are analyzed, for better insight into the potential of AMPK as a therapeutic target.